Planning for Academic Supervision of Madrasah Heads in Improving Teacher Performance at MTs Mathla'ul Anwar Tempel Rejo - Fatahillah, Zahid; Zainuri, Ahmad (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2026)
This study aims to describe and analyze the academic supervision planning of madrasah heads and its impact on improving teacher performance at MTs Mathla'ul Anwar Tempel Rejo, Kedondong District, Pesawaran Regency, Lampung. The research is motivated by the limited study of academic supervision in rural private madrassas based on Islamic community organizations, especially in the aspect of supervision planning. The research uses a qualitative approach with a descriptive case study type. The research informants consisted of the head of the madrasah and six teachers who were selected through the purposive sampling technique. Data collection was carried out through in-depth interviews, participatory observations, and documentation studies. Data analysis uses the interactive model Miles, Huberman, and Saldaña which includes data condensation, data presentation, and conclusion drawn. The results of the study show that academic supervision is carried out in a flexible, humanistic, and collaborative manner through supervision planning, class visits, examination of learning tools, post-supervision dialogue, and follow-up of teacher coaching. Academic supervision has a positive impact on improving work discipline, learning quality, completeness of learning administration, and variations in teachers' teaching methods. However, the implementation of supervision still faces obstacles in the form of limited time for madrasah heads, the lack of standard supervision instruments, and the low technological competence of some teachers. This research produced a relevant contextual academic supervision model based on teacher needs applied to rural private madrasas.